-10
6(5-3x)=7(10-2x). Plug -10 into each x and use PEMDAS which is Parentheses, Exponents, Multiplication, Division, Addition, and Subtraction.
Plugging -10 in would look like: 6(5-3(-10))=7(10-2(-10)).
What you want to do is solve one side so lets solve the right side first: 2· -10 = -20. 10-(-20)= 10+20= 30. 7 · 30=210. Now that we have this side figured out it will be easier to figure the rest out.
3 · -10= -30. 5 - (-30)= 5+30=35. 6·35=210. Both sides come to out to be the same thing using -10.